Manajemen Sumber Daya Manusia Pada Lembaga PAUD (Studi Kualitatif) Di Kota Samarinda - Brantasari, Mahkamah; Hanita, Hanita (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2020)
PAUD institutions as an organization engaged in early childhood education are an activity that aims to educate human life, especially students, so that in its implementation it is necessary not only to have a planning related to teaching and learning activities but also an integral process that involves several factors, namely: educational goals, educators, students, learning tools and the environment. PAUD institutions should pay attention to the human resources they have, in running their organizations it is certainly inseparable from human resources that must improve both in terms of knowledge, skills and abilities in managing PAUD institutions. This study focuses on the process of educational human resource management, namely educators and education personnel, maintaining human resources who are serious in their work, can provide enthusiasm for inspiration, resulting in productive employees towards the organization, and managerial strategies. In this study the authors conducted a qualitative study by conducting semi-structured interviews in which the authors collected data with a focus on the institution under study, the research was carried out at PAUD institutions in the city of Samarinda.